2021
DOI: 10.1101/2021.03.22.21254081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 reinfection: A Rapid Systematic Review of Case Reports and Case Series

Abstract: The COVID-19 pandemic has infected millions of people worldwide and many countries have been suffering from a large number of deaths. Acknowledging the ability of SARS-CoV-2 to mutate into distinct strains as an RNA virus and investigating its potential to cause reinfection is important for future health policy guidelines. It was thought that individuals who recovered from COVID-19 generate a robust immune response and develop protective immunity, however, since the first case of documented reinfection of COVI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…Although the risk of re-infection appears to be low in humans, there are reports of varying disease severity in re-infected individuals. 9,11,15,16 Wang et al, 2021 has reported 68.8%, 18.8% and 12.5% of similar, worse and mild disease severity in re-infection cases. 11 Severe disease has also been reported with Delta variant re-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of re-infection appears to be low in humans, there are reports of varying disease severity in re-infected individuals. 9,11,15,16 Wang et al, 2021 has reported 68.8%, 18.8% and 12.5% of similar, worse and mild disease severity in re-infection cases. 11 Severe disease has also been reported with Delta variant re-infection.…”
Section: Discussionmentioning
confidence: 99%
“… 14 These cases show a high diversity in clinical presentation, varying from asymptomatic infection to severe disease, although a publication bias for more severe cases is certainly conceivable. 15 Because the exact pathogenesis of MIS-C remains elusive, it is currently unknown if immunologic memory will prevent recurrence of MIS-C upon reinfection with SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…The average time duration between first infection and reinfection in our review was 63.6 days. Wang et al in their review noted it to be 76 days[99] whereas Manish et al in their review[100] observed a lengthier duration of median 113.5 days. This variation in time duration outlines the need for vigilance when it comes to COVID-19 reinfection, especially considering waning antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst our review did not analyze the cause of reinfection being due to different variants, they cannot be excluded. A review by Wang et al[99] concluded that previous COVID-19 reinfection did not confer total immunity and a second infection by a different variant was possible with the second infection being more severe than the first. Even though most of the studies in our review predated the announcements of the new variants, however, given the ability of the virus to mutate at a rapid pace, some reinfection cases reported in our study could be due to the variants which would have resulted in more severity of reinfection.…”
Section: Discussionmentioning
confidence: 99%